Perception of unrelated microbe-associated molecular patterns triggers conserved yet variable physiological and transcriptional changes in Brassica rapa ssp. pekinensis. (1st November 2020) - Kim, Wanhui; Prokchorchik, Maxim; Tian, Yonghua; Kim, Seulgi; Jeon, Hyelim; Segonzac, Cécile
Abstract: Pattern-triggered immunity (PTI) includes the different transcriptional and physiological responses that enable plants to ward off microbial invasion. Surface-localized pattern-recognition receptors (PRRs) recognize conserved microbe-associated molecular patterns (MAMPs) and initiate a branched signaling cascade that culminate in an effective restriction of pathogen growth. In the model species Arabidopsis thaliana, early PTI events triggered by different PRRs are broadly conserved although their nature or intensity is dependent on the origin and features of the detected MAMP. In order to provide a functional basis for disease resistance in leafy vegetable crops, we surveyed the conservation of PTI events in Brassica rapa ssp. pekinensis . We identified the PRR homologs present in B. rapa genome and found that only one of the two copies of the bacterial Elongation factor-Tu receptor (EFR) might function. We also characterized the extent and unexpected specificity of the transcriptional changes occurring when B. rapa seedlings are treated with two unrelated MAMPs, the bacterial flagellin flg22 peptide and the fungal cell wall component chitin. Finally, using a MAMP-induced protection assay, we could show that bacterial and fungal MAMPs elicit a robust immunity in B. rapa, despite significant differences in the kinetic and amplitude of the early signaling events. Our data support the relevance of PTI for crop protection and highlight specific functional target for disease resistance breeding in Brassica crops.